Strategi Guru SKI dalam Membentuk Karakter Kedisiplinan pada Kelas VII di MTSN 03 Bengkulu Utara - Farizza Mutiarani; Rere Melaningsi; Omilia Contesa Hamdati; Alimni Alimni (GHAITSA : Islamic Education Journal, 2024)
The purpose of this study is to discover teachers' ways for developing disciplinary character that is focused on SKI learning. The descriptive qualitative method was employed in this investigation. The findings of the study indicate that the teacher's strategy for developing the disciplinary character of class VII children, particularly in SKI learning, is not yet complete, because 1) students do not follow the discipline rules in class, 2) some students arrive late to school, 3) they do not submit assignments on time, and 4) they are sleepy during class hours. Where these four signs create an issue during the SKI learning process, more coaching is required so that youngsters can develop into disciplined individuals. The teacher's technique is to 1) create learning plans and tools, 2) implement the value approach, 3) establish class norms, and 4) instill habits. Even though there are still pupils who do not reply, it is hoped that kids can be disciplined in this manner. Students can, however, improve their habits with time.